Informe de actividades realizadas para el proyecto PNR-CIAT en los departamentos de Cordoba y Sucre, periodo junio-diciembre 1990 - Ortega, JJ (International Center for Tropical Agriculture, 1991)
In Sucre and Cordoba, activities were coordinated by the cassava teams of both departments and concentrated on the promotion of farmer groups, training, project design, and assistance in commercialization. Seven cooperatives have been organized in both departments, all wanting to operate demonstration cassava drying plants. A 1000-m(2) cassava drying plant will be constructed in San Andres de Sotavento, which will be administrated by representatives of 35 Indian groups, ACORISAN, which also receives training. A seed multiplication project with var. Venezolana was also proposed. Likewise, CIAT collaborated with the proposal of a 1000-m(2) drying plant in San Marcos, which was approved. (AS (extract)-CIAT)